1980
DOI: 10.1016/s0022-0728(80)80075-1
|View full text |Cite
|
Sign up to set email alerts
|

Initial stages of anodic oxidation of polycrystalline copper electrodes in alkaline solution

Abstract: The first stages of the anodic oxidation of polycrystalline copper electrodes in NaOH solutions were studied by potential sweep voltammetry and ellipsometry. Formation of bulk Cu20 was found to be preceded by electrosorption of oxygen species, that occurs in two successive stages, each represented by a current peak, corresponding to a different submonolayer state with a different adsorption energy. This surface oxide was formed via random electrodeposition. The width of the first current peak indicates the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
63
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 28 publications
(7 reference statements)
9
63
0
Order By: Relevance
“…In both cases the data were recorded in 0.15 mol dm −3 NaOH. Both the bulk copper and the copper-polyaniline electrodes display the various well-defined characteristic copper oxide/hydroxide formation peaks [23][24][25]. In particular, the oxidation peak at −0.38 V/(Ag|AgCl) represents the conversion of Cu to Cu(I).…”
Section: Preparation and Electrochemical Characterization Of The Modimentioning
confidence: 99%
“…In both cases the data were recorded in 0.15 mol dm −3 NaOH. Both the bulk copper and the copper-polyaniline electrodes display the various well-defined characteristic copper oxide/hydroxide formation peaks [23][24][25]. In particular, the oxidation peak at −0.38 V/(Ag|AgCl) represents the conversion of Cu to Cu(I).…”
Section: Preparation and Electrochemical Characterization Of The Modimentioning
confidence: 99%
“…Thus the electrode surface is assumed to be covered with Zn(OH)z layer before the potential scan. Comparing the anodic peaks recorded at potentials > -1.00V for e-brass (in this study) with those reported previously for copper shows that: (a) peak A~ corresponds to the formation of a Cu(OH) film [29][30][31]; (b) peak (or shoulder) A2 is assumed to be due to transformation of Cu(OH) to Cu20 [29]; (c) peak A2 is related to the formation of a Cu(OH)2 or CuO layer [29,30,32]; and (d) peak A 3 (shown only in highly alkaline solutions) is attributable to the oxidation of Cu(II) species to Cu(III) species [33,34].…”
Section: Cyclic Voltammetrymentioning
confidence: 99%
“…In a study of the initial stages of anodic oxidation of polycrystaUine copper electrodes in alkaline solutions [1 ], we measured potential sweep voltammetry curves which show that formation of bulk Cu~O is preceded by electrosorption of oxygen species. The electrosorption occurs in two successive stages, each represented by a current peak, corresponding to a different submonolayer state with a different adsorption energy.…”
Section: Introductionmentioning
confidence: 99%